2008
DOI: 10.1016/j.cemconres.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of traversing crack on chloride diffusion into concrete

Abstract: International audienceThis study examined the effects of traversing cracks of concrete on chloride diffusion. Three different concretes were tested: one ordinary concrete (OC) and two high performance concretes with two different mix designs (HPC and HPCSF, with silica fume) to show the influence of the water/cement ratio and silica fume addition. Cracks with average widths ranging from 30 to 250 mu m, were induced using a splitting tensile test. Chloride diffusion coefficients of concrete were evaluated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
199
3
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(228 citation statements)
references
References 8 publications
13
199
3
13
Order By: Relevance
“…Therefore, the findings of this study are not expected to be substantially influenced by this approximation since the effect of the added microcracks would be far greater than that of the ITZ. Indeed, the order of magnitude increase in transport property simulated in this study is well within the range of those reported in the literature [Jacobsen et al 1996;Djerbi et al, 2008;Wong et al, 2009;Kamali-Bernard and Bernard, 2009;Wu et al, 2015] Ideally our simulated results would be compared with experimental measurements. However, the availability of such experimental data that are suitable for direct comparison is at best scarce and probably non-existent.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the findings of this study are not expected to be substantially influenced by this approximation since the effect of the added microcracks would be far greater than that of the ITZ. Indeed, the order of magnitude increase in transport property simulated in this study is well within the range of those reported in the literature [Jacobsen et al 1996;Djerbi et al, 2008;Wong et al, 2009;Kamali-Bernard and Bernard, 2009;Wu et al, 2015] Ideally our simulated results would be compared with experimental measurements. However, the availability of such experimental data that are suitable for direct comparison is at best scarce and probably non-existent.…”
Section: Discussionsupporting
confidence: 65%
“…Many previous studies have examined the influence of cracks on mass transport properties of concrete such as the work of Jacobsen et al [1996], Wang et al [1997], Gerald et al [1997,2000], Aldea et al [1999], Kamali-Bernard and Bernard [2009], Picandet et al [2009], Grassl et al [2010], Jang et al [2011], Akhavan et al [2012] and Djerbi et al [2008Djerbi et al [ , 2013. However, the majority of the available studies relate to large (> 0.1 mm) traversing cracks that go through the entire thickness of the sample.…”
Section: Introductionmentioning
confidence: 99%
“…<Insert According to the results of Djerbi et al [24], Idiart et al [4] proposed that in a completely cracked medium, the diffusion coefficient tends to reach the diffusivity in free solution.…”
Section: <Insert Fig 3>mentioning
confidence: 99%
“…A considerable amount of effort has been devoted to the modelling of chloride ions transport mechanisms (diffusion, migration, convection) and behaviour within cement materials. However, chloride transport modelling is reliable only if the main degradation factor of concrete structures into service, i.e., cracking, is considered (see ( [6]) and ( [7])).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the coupling, researchers link an equivalent diffusion coefficient D e to a crack width parameter. They propose models depending on this coefficient fitted in experimental data (see ( [11]), ( [6]) and ( [8])). ( [11]) and ( [6]) suggest a linear relationship between the crack width and the equivalent diffusion coefficient D e .…”
Section: Introductionmentioning
confidence: 99%